Development of Questionnaire on Supplier Selection Criteria for Textile and Apparel Industry – A Case Study in Vietnam - Nhu Mai Thi Nong; Phong Thanh Ho (International Journal of Supply Chain Management, 2019)
Supplier selection criteria are of importance in supplier selection because of their impact on the input materials and production progress of purchasers. However, there is a dearth of researches on a well-designed and validated questionnaire to assess supplier selection criteria for textile and apparel sector in general and for Vietnamese textile and apparel industry in particular. Therefore, the purpose of this study was to develop a questionnaire to assess those criteria with their level of importance. An integrated approach of qualitative and quantitative was employed in the study. First, the qualitative approach involving purposeful sampling and theoretical sampling was used to explore what supplier selection criteria Vietnamese textile and apparel companies were utilizing after the literature on supplier selection criteria had been reviewed. Next, a prequestionnaire was built and sent to some practitioners and experts for their revision. Then, a pilot survey of 31 companies was conducted in Vietnamese textile and apparel companies to determine the supplier selection criteria that are best suited for Vietnamese textile and apparel companies. Numerous statistical tests were conducted to validate the results which will be a good contribution to the selection process of textile and apparel companies, especially Vietnamese companies. They can utilize the questionnaire as a tool to set their supplier selection criteria.